سد الذرائع وتطبيقاتها المعاصرة في المجال الاجتماعي - Sultan Ali Thabet Hasan Algrade (Al-Zahra : Journal for Islamic and Arabic Studies, 2022)
This research aims to demonstrate the great importance of the evidence of sadd al-zarai’ (avoid doing destructions), and its application to some contemporary social models. This research employs the inductive and analytical approach. The research contained an introduction, three sections and a conclusion. The first and second sections talked about the concept of sadd al-zarai’, indicating the definition, the pillars, the conditions and the parts. The third section was applied to some social models and the extent to which the controls were achieved to sadd al-zarai’ in them, and began by mentioning applied models from the Qur’an, the Sunnah, and the contemporary reality which included three models: Hajj and Umrah in light of the spread of the Corona virus (Covid 19 -), Qat in Yemen, and the Prophet’s birthday. This article found that sadd al-zarai’ is a legitimate argument based on the Holy Qur’an, the Prophet’s Sunnah and the work of the Companions. Also, that sadd al-zarai’ is complementary to maslahah mursalah, through which the tolerance of Islamic law, its expansion and validity for every time and place is confirmed by: bringing interests and multiplying them, preventing and minimizing destructions, and showing its great impact in containing jurisprudential developments and emerging issues in various fields, especially social field, through the diversity of sources of ijtihad and deduction.